SISTEM INFORMASI KEPERAWATAN PADA RUMAH SAKIT DR AK GANI DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Jei Yehezkiel Karo Sekali; Nyimas Sopiah (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Abstract : The information age is a period that involves a lot of information in decision making, both by individuals, companies and government agencies. The data is processed using a well-integrated system to produce an accurate and useful information system. To manage nurses, as well as perform duty shift attendance, and also make reports already using computerization, the head nurse only monitors the nurse's activities, the system development method uses RAD, the programming language PHP and MySQL as the database, the results that can be achieved are between nursing and the head nurse can well integrated.